A REVIEW OF THE RECENT RESEARCH ACTIVITIES IN THE FILD OF ELECTRICAL DISCHARGE MACHINING - OANA-GEORGETA GHIORGHE; CAROL SCHNAKOVSZKY; MARIA-CRINA RADU; CATALIN NICOLAE TAMPU; BOGDAN NITA (Journal of Engineering Studies and Research, 2024)
Electrical discharge machining (EDM) is one of the earliest non-traditional machining processes being considered one of the most popular machining methods today. The EDM process basis on thermoelectric energy between the workpiece and an electrode, so that the discharge energy generated during the operation characterizes the productivity of the process. Due to the well-established machining options utilized in the industry of aerospace, automotive industry and surgical components for precision machining and making complex geometrical shapes in hard-to-cut materials, a significant amount of research interests has been created in this field. This paper provides a review of numerous academic research activities carried out in the previous years, as well as numerous developments in the field of EDM related to increased machining rates, improved performance, materials and dielectrics used, electrode design and manufacture.